Nicotine and Cognitive Efficiency in Alcoholics and Illicit Stimulant Abusers: Implications of Smoking Cessation for Substance Users in Treatment - Ceballos, Natalie A.; Tivis, Rick; Lawton-Craddock, Andrea; Nixond, Sara Jo (Substance use & misuse, 2006)
Cigarette smoking is prevalent among alcoholics and illicit substance abusers. However, the potentially confounding effect of nicotine on studies of cognition in detoxified substance users has rarely been addressed. In the current study of 87 participants, behavioral and electrophysiological indices of cognitive efficiency were measured in tobacco smokers from four groups: alcoholics, illicit stimulant abusers, concurrent abusers, and control subjects. Data were collected from 2001 to 2003. We hypothesized that acute nicotine administration would modify cognitive deficits in alcoholics and illicit stimulant abusing groups. An adaptation of the Rapid Visual Information Processing task was administered after stabilization of nicotine levels via a high- or low-dose transdermal nicotine patch. Across groups, increased nicotine dose was associated with decreased reaction time (p =. 03). A group × nicotine dose interaction trend was noted in which increased nicotine was associated with increased correct responding within the alcoholic group (p =. 02). No significant differences in electrophysiology were observed. These results suggest that nicotine may modify cognitive efficiency in alcoholics and illicit stimulant abusers, a concept with relevance to both the design of experimental work and the treatment of alcohol and illicit stimulant dependence. Further work is needed to determine whether this effect predominantly reflects facilitation of cognition function or alleviation of nicotine withdrawal.